Fear extinction induces maladaptive generalization via noradrenergic and GABAergic systems - Aiqiu Zheng; Dan Yu; Xin Meng; Shumin Gong; Jiale Ye; Hui Zhou; Mo Chen; Shuming An; Jun Ma; Can Li; Jun-Li Cao; Kunwei Wu (Proceedings of the National Academy of Sciences, 2026)
Exposure therapy for anxiety disorders relies on fear extinction to reduce pathological fear responses. Here, we show that while effective at diminishing conditioned fear, extinction training paradoxically enhances fear generalization to safe stimuli through activation of the locus coeruleus–dentate gyrus (LC-DG) noradrenergic circuit. Specifically, LC norepinephrine release during extinction stimulates DG GABAergic neurons via β1-adrenergic receptors, engaging a PKA/CREB-dependent signaling cascade that ultimately leads to α4-GABA A R-mediated inhibition of granule cells and impaired threat discrimination. Genetic ablation of α4-GABA A R confirms their essential role. Crucially, this generalization can be prevented by targeting the pathway at distinct points: β1-AR blockade immediately after extinction or pharmacological inhibition of the PKA/CREB signal during the same postextinction window. These findings reveal that extinction produces competing neural consequences—adaptive fear suppression coupled with LC-DG-mediated maladaptive generalization. The identified molecular targets and their critical timing windows provide a neurobiological framework for improving exposure-based therapies.